ACTIVATION OF GENES CONTROLLING THE IMMUNE SIGNALING PATHWAYS: DIFFERENTIAL INDIVIDUAL SENSITIVITY OF HUMAN BLOOD CELLS FOR INTERFERON PREPARATIONS AND IFN INDUCERS - T. M. Sokolova; A. N. Shuvalov; I. M. Shapoval; Z. A. Sokolova; F. I. Ershov (Медицинская иммунология, 2015)
We have studied dose effects of several Interferon (IFN) inducers, i.e., Genfaxon (beta-1 IFN), Cycloferon and Immunomax upon expression of six genes controlling the signaling in immune pathways (TLR3, TLR4, RIG1, IRF3, IPS, B2M), by means of real-time RT-PCR, being tested with blood cells from three humans. It is revealed that individual cell samples showed different sensitivity to these drugs, probably, due to constitutive levels of TLR3 and TLR4 gene expression and possible connections with their immune pathology. Genfaxon at a dose of 104 ME produced potent stimulation of TLR3, TLR4, IRF3 and B2M genes in two persons. Immunomax, at a dose 0,5 unit, exhibited same effect in one case only (with Epstein-Barr virus infection). Cycloferon stimulated gene expression at much lower levels than Genfaxon in any cases. We have shown a reverse correlation between sensitivity of the cells to Immunomax, and constitutive TLR3 and TLR4 expression. The stimulatory effects of Immunomax were maximal in a person with very low TLR3/4 gene expression. Immunomax boosted the genes from several signaling pathways, including TLR3, TLR4, but genes of RIG/IPS pathway showed higher activation. Cycloferon induced gene transcription of IRF3 and B2M-receptor to higher degree, than expression of TLR3 and TLR4 genes. Hence, our data concerning Genfaxon, Immunomax and Cycloferon confirm their IFN-inducing effects upon human blood cells. The RT-PCR-based evaluation of gene expression related to signaling immune pathways in blood cell populations will enable rapid and highly specific quantitation of IFN and IFN-inducer drugs activities, thus avoiding their biological testing in long-term cell cultures.